Predator control alters wolf interactions with prey and competitor species over the diel cycle. Issue 8 (13th May 2022) - Frey, Sandra; Tejero, Daniel; Baillie‐David, Katherine; Burton, A. Cole; Fisher, Jason T.
Abstract : Predator control remains one of the most common strategies for the conservation of threatened prey species. Despite significant and ongoing efforts to reduce predator populations, little is known about the impacts on the behaviour and interactions of target and non‐target species following numerical and potentially behavioural suppression of predators. We used camera‐trap data collected before and after an intensive wolf control program in northeastern Alberta's boreal forest to evaluate changes in activity patterns and overlap in wolves, competitors and prey. We hypothesized wolves would shift their activity toward increased nocturnality to avoid diurnal control efforts, and thereby cause a behavioural cascade where other species shift activity to maintain temporal segregation from wolves. Wolves shifted activity into the nighttime following predator control, reducing temporal overlap with the other, mostly diurnal, members of the community. Decreases in activity overlap between wolves and other species indicates reduced potential for wolf interactions with ungulate prey and large competitor species. Predator control may therefore not only release species from top to down regulation and competition following numerical suppression of top predators, but also through de‐coupling of temporal overlap, with potential effects on species interactions. Understanding the indirect impacts of conservation strategies such as predator control on both target and non‐target species provides insight into potential disruptions to top–down regulation and the associated species interactions that shape community structure.